Next steps in untangling the web of violence: a research agenda - Hamby, Sherry L. (Child maltreatment, 2021)
In this commentary, we outline four key trends in violence and trauma research and describe needed research to advance our ability to understand, prevent, and respond these problems. The trends are the move toward evidence-based policy, the recognition of the importance of trauma dosage, the shift to strengths-based approaches, and increased attention to race, gender, and other personality and community characteristics regarding health disparities and culturally appropriate interventions. For each trend, we have identified needed research areas, taking care to identify low-resource and high-resource studies that can help us reduce the burden of trauma.